2019
DOI: 10.1155/2019/7395784
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyles, Depression, Anxiety, and Stress as Risk Factors in Nursing Apprentices: A Logistic Regression Analysis of 1193 Students in Lima, Peru

Abstract: Currently, it is considered that mental disorders are related to different types of chronic pathologies; for this reason, efforts to improve general health should also focus on preserving mental health. Therefore, the objective of this study was to determine through logistic regression if the independent variables (risk factors) such as (X1) age, (X2) sex, (X3) marital status, (X4) number of children, and (X5) occupation have influence on the dependent variables such as lifestyles, depression, anxiety, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 22 publications
(34 reference statements)
0
20
1
10
Order By: Relevance
“…The chi-square test in this study reveals that there was a significant association found between stress level and marital status, and duration of hypertension physical activity (P<.05). However, a study was carried out by Diaz-Godino, et al evidenced that there was a significant association between anxiety and marital status (P=0.043) [21]. Also, there was a significant association found between systolic BP and education, family type, and physical activity (P<.05) in this present research.…”
Section: Discussioncontrasting
confidence: 51%
“…The chi-square test in this study reveals that there was a significant association found between stress level and marital status, and duration of hypertension physical activity (P<.05). However, a study was carried out by Diaz-Godino, et al evidenced that there was a significant association between anxiety and marital status (P=0.043) [21]. Also, there was a significant association found between systolic BP and education, family type, and physical activity (P<.05) in this present research.…”
Section: Discussioncontrasting
confidence: 51%
“…Em 44 (95,6%) dos estudos selecionados, tal avaliação ocorreu por meio de algum instrumento (Akca, Arslan, Baser, & Kuzucu, 2015;Alshammari, 2019;Amr, El-Gilany, El-Moafee, Salama, & Jimenez, 2011;Baksi, Gumus, & Zengin, 2017;Cheung et al, 2016;Diaz-Godiño et al, 2019;El-Bilsha, 2012;Hollenbach, 2016;Hsiung, Tsai, Chiang, & Ma, 2019;Khawaja, Chan, & Stein, 2017;Maghaminejad et al, 2020;Marchi et al, 2013;Messineo et al, 2015;Mohamadkhani, Alipor, & Hasanzadeh, 2013;Mojarrab, Bazrafkan, & Jaberi, 2020;Plaiti et al, 2016;Samson, 2019;Savitsky, Findling, Ereli, & Hendel, 2020;Silva, Chaves, Duarte, Amaral, & Ferreira, 2016;Son, So, & Kim, 2019;Souto et al, 2012;Sun et al, 2020;Teixeira et al, 2014;Turan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Já a DASS-21 avalia respostas de acordo com a semana anterior ao dia em que o instrumento é aplicado. Este subdivide-se em três subescalas: depressão (DASS-D), ansiedade (DASS-A) e estresse (DASS-S), com quatro opções de respostas entre 0 (nada se aplica a mim) e 3 (aplica-se muito a mim e a maior parte do tempo) (Barraza et al, 2015;Cheung et al, 2016;Diaz-Godiño et al, 2019;Rathnayake & Ekanayaka, 2016;Walailak et al, 2018).…”
Section: Referênciasunclassified
“…In a study conducted with a large student population in the United States, female nursing students expressed higher levels of anxiety symptoms than female students in other professions 26 . In a study conducted with 1193 nursing students in Peru, ages between 20 and 29 years were a risk factor for both depression and anxiety, and being a woman was a risk factor for anxiety 27 . Considering the rates of mental illness in the world, women are more affected by depression than men 28 .…”
Section: Discussionmentioning
confidence: 99%